Microcomputer Controlled Dual Slope Delta Modulated Three Phase Inverter - Ramdan , Razali (2001)
Experiments have been carried out by online microcomputer operation of the inverter to verify the claim of improved performance of delta modulated inverter by dual slope and dual slope-variable window width operation of the delta modulator.